Two new tetrahydrofuran derivatives from the fungus Mucor spp. SNB-VECD11D isolated from the Chrysomelidae Acalymma bivittula. Issue 38 (20th September 2017) - Touré, Seindé; Dusfour, Isabelle; Stien, Didier; Eparvier, Véronique
Graphical abstract: Highlights: The fungus Mucor spp. produces two tetrahydrofuran diterpenes mucorinic acids A and B. Mucor spp. produces resin acid dehydroabietic acid and analogues. Mucorinic acids A and B presented interesting antibacterial potential. Abstract: Two new tetrahydrofuran derivatives, mucorinic acids A (1 ) and B (2 ) as well as the three known secondary metabolites dehydroabietic acid (3 ), Δ8-dihydroabietic acid (4 ) and 8-pimarenic acid (5 ) were isolated from a solid culture of the fungus Mucor spp. isolated on insect Acalymma bivittula . The structure of these compounds was elucidated by analysis of NMR and MS spectroscopic data. Compounds were tested in antimicrobial and insecticidal assays. Dehydroabietic acid exhibited moderate larvicidal activity on Aedes aegypti larvae with 65% mortality at 10 ppm. Both new compounds1 and2 showed interesting antibacterial activity on Staphylococcus aureus and methicillin resistant S. aureus with MIC values in the 8–16 μg/ml.